“Thigh in the Sky”: Canadian Pacific Dresses Its Female Flight Attendants - Sangster, Joan; Smith, Julia (Labor, 2017)
This article uses a case study of a highly publicized 1970 controversy over Canadian Pacific Air Lines’ flight attendant uniforms—specifically, a switch from mini to midi skirt—as a case study in business-labor relations concerning the regulation of women workers’ bodily appearance. Using company and union records and employing a historical, materialist, and feminist analysis, we trace how notions of aesthetic and emotional labor changed over time in relation to the political economy, gender ideologies, and the agency of workers themselves. The flight attendants’ reluctance to challenge the airline’s sexist advertising indicated how both accommodation and resistance were intertwined in complex ways in the workplace. Their acceptance of more “thigh in the sky” had much to do with a highly regulated and disciplined workplace, an entrenched division of labor on the airplane, and gendered notions of beauty and glamour in the industry, including women’s strategic use of beauty on the job to their own advantage.